(untitled) (Global Journal of Computer Science and Technology, 2012)
The bounded oil reserves and the need to reduce environmental pollution bordering increasingly to make solution proposals to combat the problem by reducing environmental pollution and on the other hand seek sustainability with energy savings and better quality of life for Mexicans in this paper propose alternatives to reduce fuel use and greater use of renewable energy using photovoltaic systems Unquestionably the Mexican political issue in energy will be a little difficult to treat however proposals are sustainable use solar energy leaving a balance profitable for Mexican society in the field of electromobility and basic needs such as what is the purification of water with the search for alternatives to solve a social problem purified water consumption in rural areas where currently burning firewood to boil water creates irreversible effects pollutants and respiratory diseases to solve the environmental problem raises renewable energy use using photovoltaic power systems the same systems can also be used to replace the use of fossil energy and also have the advantage over fossil fuels that are able to reach the most remote and isolated areas where needs are not yet covered which is why the great importance of the benefits offered substantial PV systems for social benefit